المعالجة المحاسبية و الجبائية لعقود الإمتياز- دراسة حالة لمؤسستين خاصة و عمومية بولاية سيدي بلعباس - حمادي مليكة; أورنيدي سندس (جامعة الوادي University of Eloued, 2024)
دفت هذه الدراسة إلى معرفة المعالجة المحاسبية والجبائية لعقد الامتياز بين ما تنص عليه القوانين والقواعد المتعارف عليها وبين ما هو معمول به لدى المؤسسات باعتبارها المستفيد، بالإضافة إلى معرفة المعالجة المحاسبية المتبعة من طرف الدولة كونها المصلحة المتعاقدة والمانحة لحق الامتياز. من أجل معالجة الاشكالية قمنا بدراسة ميدانية لدى مؤسستين متحصلتين على اصول عقارية في اطار عقد الامتياز للمقارنة ودراسة أوجه الاختلاف بينهما. خلصت الدراسة إلى أن تطبيق المعالجة المحاسبية والجبائية لعقد الامتياز يعتمد على التحكم في القواعد المحاسبية والجبائية والقوانين المتعلقة به لضمان تنفيذ شروط منح حق الامتياز. This study aimed to explore the accounting and tax treatment of the franchise contract between what is stipulated by the laws and regulations and what is actually applied in the economic institutions as the main recipient. In addition, the study tries to shed light on the accounting treatment used by the government as it is considered the contracting and franchising authority. In order to answer the main question of the work, we opted for a field study with two institutions that were granted real estate assets within the framework of the franchise contract to examine the differences between them. The results demonstrated that the application of the accounting and tax treatment of the franchise contract depends mainly on the awareness and good knowledge of accounting and tax regulations related to the franchise contract to ensure the implementation and compliance with the conditions forgranting the franchise
Accounting and fiscal treatment of concession contracts -a case study of two private and public institutions in the state of Sidi Bel Abbes
Keywords: عقد الامتياز; محاسبة مالية; محاسبة عمومية; جباية; franchise contract; financial accounting; public accounting; tax